2014
DOI: 10.1080/15459624.2013.858818
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm for Determining Contact Area Between a Respirator and a Headform

Abstract: The contact area, as well as the contact pressure, is created when a respiratory protection device (a respirator or surgical mask) contacts a human face. A computer-based algorithm for determining the contact area between a headform and N95 filtering facepiece respirator (FFR) was proposed. Six N95 FFRs were applied to five sizes of standard headforms (large, medium, small, long/narrow, and short/wide) to simulate respirator donning. After the contact simulation between a headform and an N95 FFR was conducted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Coffey et al 17 measured the TIL for 21 models of N95 respirators on 25 different subjects and observed that the TIL value could be as high as 88% in the absence of fit testing. Lei et al 18 and Cai et al 15 developed a “contact pressure” model to estimate gaps between the face and N95 respirators. Cai et al 14 evaluated the effect of facial expression on contact characteristics between an N95 filtering facepiece respirator and a headform.…”
Section: Introductionmentioning
confidence: 99%
“…Coffey et al 17 measured the TIL for 21 models of N95 respirators on 25 different subjects and observed that the TIL value could be as high as 88% in the absence of fit testing. Lei et al 18 and Cai et al 15 developed a “contact pressure” model to estimate gaps between the face and N95 respirators. Cai et al 14 evaluated the effect of facial expression on contact characteristics between an N95 filtering facepiece respirator and a headform.…”
Section: Introductionmentioning
confidence: 99%
“…The approach does not provide reliable isolation of worker's respiratory organs by means of dust respirators and requires the proper studies for digital models development of half masks surfaces to correct their design according to anthropometric parameters of the person's face.Besides, the unification of half masks design to provide fast production with respect to their functions under the working conditions is one of the trends of product-line expansion for IRPD. This results in need of algorithm development for computer assisted design enabling fast corrections and final product prototype [5]. It is important to control the performance of different components of dust respirators continuously both at the stages of design and exploitation; this requires the development of the proper control methods of IRPD operating parameters [6].…”
Section: Fig 2 Distribution Of Users' Faces Into 5 Groups Accordingmentioning
confidence: 99%
“…Постійне вдосконалення засобів захисту органів дихання також вимагає додаткових досліджень енерго-вират гірників під час вуглевидобутку (Campbell, Coffey & Lenhart, 2001;Clayton, 2002;Janssen, Nelson, & Cuta, 2007;Laney & Attfield, 2010;Lee, Grinshpun, & Reponen, 2010;Lei, Yang, & Zhuang, 2014;Golinko, Cheberyachko, Radchuk, & Cheberyachko, 2014;Golinko, Cheberyachko, Cheberyachko, & Naumov, 2014;Golinko, Cheberyachko, Yavorskaya, & Cheberyachko, 2016).…”
Section: вступunclassified